Analysis of the Effect of 4T in Pregnant Women on the Risk of Stunting - Ummi Irmadani Harahap; Desi Meliana Gultom; Evi Erianty Hasibuan (Institute of Computer Science (IOCS), 2023)
Stunting is a condition in which a person's height is less than normal based on age and gender. Height is a type of anthropometric examination and shows a person's nutritional status. Stunting is the result of chronic malnutrition that has been going on for years (Rahayu et al., 2018). Pregnancy with 4 is too risky for mother and child (Ariana, 2016). The type of research used was literature research from PK21 BKKB, South Tapanuli Regency. Researchers use a quantitative research approach. The population in this study were 15 districts using the total sampling method. The results of the Kolmogorov Smirnov normality test show that the normal probability value is 0.011 which is higher than a= 5%. The multicollinearity test for all independent variables has a VIF value of less than 10, so there are no symptoms of multicollinearity in this research model. The heteroscedasticity test for the distribution of residual data spreads randomly above and below the 0 Y axis and there is a certain pattern, it can be stated that the regression model has symptoms of heteroscedasticity. Based on the Autocorrelation Test, the values for dl and du are at a significance level of 5%, with n equal to 120 and k = 3. Using these standards, the resulting value for dl is 1.63731 and du is 1.74715. The Durbin-Watson value of 1.269 is between du ( 1.74715 ) and 4-du (4-1.74715 = 2.25285) so it can be concluded that there is no autocorrelation problem in the regression model.